Fine Mapping and Functional Analysis Reveal a Role of SLC22A1 in Acylcarnitine Transport - Kim, Hye In; Raffler, Johannes; Lu, Wenyun; Lee, Jung-Jin; Abbey, Deepti; Saleheen, Danish; Rabinowitz, Joshua D; Bennett, Michael J; Hand, Nicholas J; Brown, Christopher; Rader, Daniel J (American journal of human genetics, 2017)
Genome-wide association studies have identified a signal at the SLC22A1 locus for serum acylcarnitines, intermediate metabolites of mitochondrial oxidation whose plasma levels associate with metabolic diseases. Here, we refined the association signal, performed conditional analyses, and examined the linkage structure to find coding variants of SLC22A1 that mediate independent association signals at the locus. We also employed allele-specific expression analysis to find potential regulatory variants of SLC22A1 and demonstrated the effect of one variant on the splicing of SLC22A1. SLC22A1 encodes a hepatic plasma membrane transporter whose role in acylcarnitine physiology has not been described. By targeted metabolomics and isotope tracing experiments in loss- and gain-of-function cell and mouse models of Slc22a1, we uncovered a role of SLC22A1 in the efflux of acylcarnitines from the liver to the circulation. We further validated the impacts of human variants on SLC22A1-mediated acylcarnitine efflux in vitro, explaining their association with serum acylcarnitine levels. Our findings provide the detailed molecular mechanisms of the GWAS association for serum acylcarnitines at the SLC22A1 locus by functionally validating the impact of SLC22A1 and its variants on acylcarnitine transport.